(untitled) (Sociologisk Forskning, 2007)
New opportunities for social stratification research in Sweden: International occupational classifications and stratification measures over time The Swedish occupational classifications have in recent years been changed to a version of the international standard ISCO-88(COM), i.e. SSYK 96. As a consequence, a wide variety of internationally well-known stratification measures can be applied to Swedish data sets. In this article some tests of the validity of translation keys between the older national classifications and SSYK 96 are presented. The keys seem to work satisfactorily. Thus, it is possible to create long time-series with ISCO/SSYK and use these well-known stratification measures over time. Hence, the international interest in Swedish data sets, and empirical results based on these data sets, could rise. Moreover, in the article an empirical regularity, which is quite astonishing, is paid attention to; stratification measures based on different theoretical rationales indicate very similar hierarchies of occupations.